The Enhancement of Primary Students Mathematical Connectionsand Habits of Mind Abilities Using REACT Strategy - Fendrik, Muhammad; Alpusari, Mahmud; Yosi, Ana; Widyanthi, Astri (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to improve primary studentsâ mathematical connections and habits of mind abilities by using REACTstrategy. This research is a quasi-experimental study conducted in 003 Peranapelementary schoolin the even semester of 2017/2018. The subjects of this study were class V students. Based on the results of data analysis and findings obtained in the study, it can be concluded that there are significant differences in abilities improvement between classes that use REACT strategies and general learning with the influence of 52%. This is proved by an enhancement of studentsâ mathematical connections ability in the experimental class,by the average of initial testis 54.96 to 79.13 and in the final test with an average enhancement of 0.54 included in the medium category. Whereas the control class has an enhancement in the average of initial test from 55.67 to 64.33, and in the final test with the mean of 0.05.Meanwhile, students habits of mind abilities which include self-regulation, critical thinking, and creative thinking ability can appear in the experimental and control class even though these abilities do not appear in all students.